Endothelial-Related Biomarkers in Evaluation of Vascular Function During Progression of Sepsis After Severe Trauma: New Potential Diagnostic Tools in Sepsis - Yang B; Wang X; Liu Z; Lu Z; Fang G; Xue X; Luo T (Journal of Inflammation Research, 2023)
Biao Yang,1,* Xiaoyong Wang,2,* Zhaorui Liu,1,* Zhengmao Lu,1 Guoen Fang,1 Xuchao Xue,1 Tianhang Luo1 1Department of General Surgery, Changhai Hospital, The Second Military Medical University, Shanghai, 200433, People’s Republic of China; 2Department of Gastrointestinal Surgery, People’s Hospital of Haimen City, Nantong, Jiangsu Province, 226100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tianhang Luo, Department of General Surgery, Changhai Hospital, 168 Changhai Road, Yangpu District, Shanghai, 200433, People’s Republic of China, Tel +86-21-31161589, Fax +86-21-31161593, Email luotianhang78@126.comPurpose: This study aimed to investigate the changes in endothelial-related biomarkers and their relationship with the incidence and prognosis of patients with sepsis after severe trauma.Methods: A total of 37 severe trauma patients admitted to our hospital from Jan. to Dec. 2020 were enrolled in our research. All enrolled patients were divided into the sepsis and the non-sepsis groups. Endothelial progenitor cells (EPCs), circulating endothelial cells (CECs), and endothelial microparticles (EMPs) were detected on admission time; 24– 48 hours and 48– 72 hours after admission respectively. Demographic data, Acute Physiology, Chronic Health Evaluation (APACHE) II, and Sequential Organ Failure Assessment (SOFA) score were calculated every 24 h of admission to assess the severity of organ dysfunction. Receiver operating characteristic (ROC) curves were drawn to compare the areas under the curve (AUC) of endothelial-related biomarkers for the diagnosis of sepsis.Results: The incidence rate of sepsis was 45.95% in all patients. The SOFA score in the sepsis group was significantly higher than that in the non-sepsis group (2 points vs 0 points, P< 0.01). The number of EPCs, CECs, and EMPs all rose quickly in the early phase after trauma. The number of EPCs was similar in both groups, but the number of CECs and EMPs in the Sepsis Group was much higher than in the non-Sepsis Group (all P< 0.01). Logistic regression analysis showed that the occurrence of sepsis was closely related to the expression of 0– 24h CECs and 0– 24h EMPs. The AUC ROC for CECs in different time periods were 0.815, 0.877, and 0.882, respectively (all P< 0.001). The AUC ROC for EMPs in 0– 24h was 0.868 (P=0.005).Conclusion: The expression of EMPs was higher in early severe trauma, and high levels of EMPs were significantly higher in patients with early sepsis and poor prognosis.Keywords: sepsis, severe trauma, endothelial cell, biomarkers, prognosis